2022
DOI: 10.1038/s41586-022-04499-2
|View full text |Cite|
|
Sign up to set email alerts
|

Tryptophan depletion results in tryptophan-to-phenylalanine substitutants

Abstract: Activated T cells secrete interferon-γ, which triggers intracellular tryptophan shortage by upregulating the indoleamine 2,3-dioxygenase 1 (IDO1) enzyme1–4. Here we show that despite tryptophan depletion, in-frame protein synthesis continues across tryptophan codons. We identified tryptophan-to-phenylalanine codon reassignment (W>F) as the major event facilitating this process, and pinpointed tryptophanyl-tRNA synthetase (WARS1) as its source. We call these W>F peptides ‘substitutants’ to distinguish the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 68 publications
(102 reference statements)
0
67
0
Order By: Relevance
“…While we did not directly dissect the molecular mechanisms by which Trp metabolism is regulating circadian homeostasis, previous studies have identified multiple potential underlying mechanisms, including metabolites of the kynurenine pathway acting as UV-protectant in the eye [ 59 ], the photo-protectant role of serotonergic afferents near and/or on retinal axon terminals in the SCN [ 44 ], or NMDAR which binds kynurenine metabolites to regulate behavioral responses to photic signals [ 63 ]. Another possibility is that the depletion of Trp resulted in replacement with phenylalanine during translation which subsequently alter the function of the proteins [ 64 ].Light can also enhance Trp catabolism, which yields photoproducts that may regulate the expression of circadian genes [ 65 ]. Trp photoproducts are aryl hydrocarbon receptor (AhR) agonists which regulate the expression of the core clock machinery and can form a heterodimer with Bmal1 [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…While we did not directly dissect the molecular mechanisms by which Trp metabolism is regulating circadian homeostasis, previous studies have identified multiple potential underlying mechanisms, including metabolites of the kynurenine pathway acting as UV-protectant in the eye [ 59 ], the photo-protectant role of serotonergic afferents near and/or on retinal axon terminals in the SCN [ 44 ], or NMDAR which binds kynurenine metabolites to regulate behavioral responses to photic signals [ 63 ]. Another possibility is that the depletion of Trp resulted in replacement with phenylalanine during translation which subsequently alter the function of the proteins [ 64 ].Light can also enhance Trp catabolism, which yields photoproducts that may regulate the expression of circadian genes [ 65 ]. Trp photoproducts are aryl hydrocarbon receptor (AhR) agonists which regulate the expression of the core clock machinery and can form a heterodimer with Bmal1 [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may bias HLA-I ligand predictors trained on such data, and PRIME may be correcting for this bias. Second, recent studies have demonstrated that peptides genomically encoded with a W can undergo a W>F substitution during protein synthesis (Pataskar et al, 2022). Considering that several studies used tandem mini-genes to identify neo-epitopes, we cannot exclude that some of the W-containing epitopes used in the training of PRIME were actually presented on HLA-I molecules with a W>F substitution, which contributed to overcome central tolerance and increase their immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 47,917 amino acid misincorporations in S. cerevisiae and 91,565 in E. coli , highlighting the vast amount of, yet, unexplored information in publicly available mass-spectrometry datasets. eTEL allows exploring amino acid misincorporations across different organisms and conditions that alter translation fidelity, such as aging or cancer (Pataskar et al, 2022).…”
Section: Discussionmentioning
confidence: 99%